PENGARUH DIMENSI ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK IPHONE DI KOTA KENDARI - Natashya, Anggita; Nasrul, Nasrul; Mokodompit, Eliyanti Agus; Masri, Muhammad; Kohawan, Rivan (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis Universitas Halu Oleo, 2021)
The purpose of this study was to examine the effect of product attribute dimensions on purchasing decisions for Iphone brand mobile phones in Kendari City. The independent variables used in this study are Product Quality, Product Features, Product Design, Product Brand, Product Packaging, Product Label and Product Support Services. The dependent variable used in this study is Purchase Decision. The population of this research is Kendari City Community Employees who use iPhone products with a total sample of 50 respondents who meet the criteria using the purposive sampling method. The analytical technique used is multiple linear regression analysis with the help of the SPSS 2 program. The results of this study found that: 1) Product quality has a significant effect on purchasing decisions for the Iphone cellphone brand in Kendari City; 2) Product features have a significant effect on purchasing decisions for the Mobile Iphone brand in Kendari City; 3) Product design has a significant effect on purchasing decisions for the Mobile Iphone brand in Kendari City; 4) The product brand has a significant effect on purchasing decisions for the Iphone cellphone brand in Kendari City; 5) Product packaging has an insignificant negative effect on purchasing decisions for the Mobile Iphone brand in Kendari City; 6) Product labels have an insignificant negative effect on purchasing decisions for the Mobile Iphone brand in Kendari City; and 7) Product support services have a significant effect on purchasing decisions for the Iphone brand in Kendari City.